How to Apply HOTS-based E-learning in Higher Education? - Edy Herianto (RIRAI Publisher, 2021)
This research is qualitative research with the type of case study to describe the implementation of e-learning based on HOTS in higher education. E-learning is a necessity that must be used by lecturers when teaching at universities, especially during the current pandemic. The learning must be based on HOTS as the demands of the industrial revolution 4.0 and society 5.0, to produce prospective teachers who can guide their students to have the ability to solve problems in life. The research subjects were 196 people who took the Philosophy of Science course at the PPKN PIPS FKIP Study Program, Mataram University. Data were collected through observation techniques, interview documentation, and tests. After conducting a holistic and specific qualitative analysis, the results show that HOTS-based e-learning is carried out through the stages of preparation for the implementation of learning and evaluation for 16 learning activities. The contents of the activities include discussion of textual material, independent contextual exercises, and completing exams. During the activity, lecturers and students gave positive responses to various supporting factors and existing challenges. This activity has an impact on the acquisition of positive student learning outcomes. As a follow-up suggestion, full vigilance is needed to seek more varied activities to be actively involved in learning activities and successfully pass lectures.